SISTEM MONITORING SUHU DAN KELEMBABAN PADA ALAT PENGERING PADI BERBASIS SOLAR CELL: Teknik Elektronika - Maharani, Alika; Kusumanto, R.D.; Rahman, A. (Teknik Elektro Polsri, 2023)
ABSTRACT Grain drying is one of the post-harvest processing processes which aims to reduce the moisture content in the grain to a certain extent until dry grain is obtained according to standards in order to enter the milling process. In general, Indonesian people use traditional methods in carrying out the process of drying grain, namely by drying it under the hot direct sun. Based on this, a machine is needed to help dry this post-harvest grain so that it can dry grain with maximum results in a short time and of course still save energy. This research aims to design and make a dryer as well as be able to monitor the temperature and humidity of the grain so that the grain can be dried according to milling standards. Key words : Grain, Solar Cell, Monitoring, Dryer